The Art of Social Media - Kawasaki, Guy; Fitzpatrick, Peg (HighBridge, 2018)
By now it's clear that whether you're promoting a business, a product, or yourself, social media is near the top of what determines your success or failure. And there are countless pundits, authors, and consultants eager to advise you. But there's no one quite like Guy Kawasaki, the legendary former chief evangelist for Apple and one of the pioneers of business blogging, tweeting, Facebooking, Tumbling, and much, much more. Now Guy has teamed up with Peg Fitzpatrick, who he says is the best social-media person he's ever met, to offer The Art of Social Media-the one essential guide you need to get the most bang for your time, effort, and money. With over one hundred practical tips, tricks, and insights, Guy and Peg present a bottom-up strategy to produce a focused, thorough, and compelling presence on the most popular social-media platforms. They guide you through steps to build your foundation, amass your digital assets, optimize your profile, attract more followers, and effectively integrate social media and blogging.